Bullying, depression and social representations in the school context (Research, Society and Development, 2021)
Bullying is a phenomenon characterized by the set of acts of physical or verbal violence that occur against one or more victims, such behaviors repetitively and intentionally can trigger depressive symptoms in those involved. Thus, the objective was to apprehend the social representations elaborated by adolescents about bullying and depression. Thirty-one adolescents aged between 12 and 18 years old, from a public school participated in the research. A sociodemographic questionnaire and a semi-structured interview were used. The instruments were applied individually, the questionnaire data were analyzed using descriptive and inferential statistics. As for the interviews, the Similitude Analysis, Word Cloud and Descending Hierarchical Classification were used. Participants demonstrated multifaceted knowledge about bullying and depression, anchoring them in the conceptual, behavioral, psycho-emotional implications, types of bullying and bullying as a synonym for play. It is noteworthy that the bullying behaviors evidenced in the study were related to physical, verbal and psychological aggression, which can lead to negligence of personal hygiene, sadness, discouragement, low academic performance, family problems and lack of support. On the other hand, adolescents also pointed out bullying as a synonym for play, outlining this phenomenon as something natural. The need for more effective interventions in this context is evidenced, contemplating strategies on the awareness of the consequences of bullying and minimization of the triggered emotional suffering.